Safety amidst being risky ambulance drivers' self-efficacy, rick attitude and driving behavior on the road. - Malaga, Lovelyn P.
The study investigated the relationship between self-efficacy, risk attitude, exposure to risky on-road situations and the risk driving behaviors of ambulance drivers. Eighty-two (n=82) ambulance drivers from Iloilo and parts of Negros Occidental served as respondents of the study. The results showed significant correlations between ambulance drivers? self-efficacy, risk attitude, exposure to risky on-road situations and their risk driving behaviors. The study also explored the ambulance drivers? work experiences and performances such as driving history, self-efficacy, risky driving tendencies, perceived norms and expectations, and assessment of conflict situations. The results demonstrated support for the Triadic Reciprocal Determinism Model of Behaviors. Driver training and public education among the recommendations in the study.